Mengelola Ekspektasi Jemaat terhadap Istri Gembala: Perspektif Expectancy Violations Theory - Esther Idayanti (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. The role of a pastor’s wife often comes with high congregational expectations, ranging from demands for perfection to full involvement in church ministry. This study aims to explore the expectations faced by pastor’s wives and how they manage these pressures using Judee K. Burgoon's Expectancy Violations Theory. A survey was conducted with 112 International Full Gospel Fellowship (IFGF) pastor’s wives globally (https://ifgf.global/), employing a combination of closed- and open-ended questions. Findings reveal that the majority of respondents experience significant pressure from the congregation, particularly related to perfection, availability for ministry, and being multi-skilled. The result underscores the importance of communication training, strengthening personal relationships with congregants, and clarifying the role of the pastor’s wife within the church leadership structure. Emotional support from husbands and community among fellow pastor’s wives were also identified as crucial in coping with expectation-related pressures.Abstrak. Peran istri gembala di gereja kerap kali disertai dengan ekspektasi tinggi dari jemaat, mulai dari tuntutan kesempurnaan hingga keterlibatan penuh dalam pelayanan gereja. Penelitian ini bertujuan untuk memahami ekspektasi yang dihadapi oleh para istri pendeta dan bagaimana mereka mengelola ekspektasi tersebut berdasarkan teori Expectancy Violations dari Judee K. Burgoon. Survei dilakukan terhadap 112 ibu Gembala Gereja International Full Gospel Fellowship (IFGF) secara global (https://ifgf.global/), menggunakan kombinasi pertanyaan tertutup dan terbuka. Hasil penelitian menunjukkan bahwa mayoritas responden merasakan tekanan ekspektasi dari jemaat, terutama terkait kesempurnaan, ketersediaan untuk melayani dan kemampuan serba bisa. Temuan menekankan pentingnya pelatihan komunikasi, penguatan relasi personal dengan jemaat, serta kejelasan peran istri gembala dalam struktur pelayanan. Dukungan emosional dari suami dan keberadaan komunitas sesama istri gembala juga menjadi kunci dalam menghadapi tekanan ekspektasi.